Research Progress of Perioperative Anesthesia Management in Patients with Hypertrophic Cardiomyopathy - LIN Shuantong; SU Xiaojun; CAO Dequan (Xiehe Yixue Zazhi)
Hypertrophic cardiomyopathy, a genetic hereditary disease, is highly regarded in clinical practice due to its unique pathophysiological changes, course characteristics, and hemodynamic features. With the continuous advance of treatment methods such as medications and surgeries, the prevention, treatment and prognosis of hypertrophic cardiomyopathy has gradually improved. However, inappropriate use of positive inotropic drugs may lead to serious consequences that are difficult to reverse. Therefore, how to smoothly navigate through the perioperative period and ensure clinical safety poses a great challenge for anesthesiologists. This paper discusses the perioperative management of patients with hypertrophic cardiomyopathy, with the hope of enhancing anesthesiologists' management capabilities for this type of disease.